Applying "PLANS" Training to Increase Career Maturity of Senior High School Students - Rico Kornelius Wahani; Alphonsus Rachmad Djati Winarno; Praharesti Eriany (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2025)
Selecting and preparing for a career is crucial during a teenager's development stage. However, many students failed to complete career development tasks and illustrated lack of career maturity. This study aimed to assess the effectiveness of PLANS (advanced study planning) training in enhancing students' career maturity. This experimental research utilized a randomized pretest-posttest control design. Sixteen 11th-grade high school students with low career maturity scores were randomly divided into two groups. The evaluation of research data was conducted using the Wilcoxon signed-rank test and Mann-Whitney U Test. The study proved that (1) the intervention did not significantly increase the students' career maturity (p= 0,069); (2) there was no significant difference in career maturity levels between the control group and the experimental (p= 0,50). This indicated that the "PLANS" training had not been proven effective in increasing students' career maturity. However, the research data showed a significant impact on the attitude aspect of career maturity after the (p= 0,043). The implications are discussed further.